2022
DOI: 10.3390/coatings12070994
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Steel Slag in Road Semi-Rigid Base: A Review

Abstract: Steel slag (SS) is industrial waste, and there is a large amount of SS to be treated in China. Its disposal generates severe environmental pollution. One of the best ways to use SS is as a road base material. This paper reviews the possibility of using SS in semi-rigid base and evaluates the performance of SS base course. The interaction between three stabilizers (cement, lime–fly ash, and cement–fly ash) and SS is analyzed, and the influence of modifier content on the performance of base course is evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…When steel slag aggregate is used in road subgrade, steel slag is mostly used as an aggregate into the mix, and the performance of the mix is studied accordingly. Li et al [ 21 ] evaluated the feasibility of steel slag used in road subgrade, and analyzed the interaction between different stabilizing materials and steel slag as well as the relationship between stabilizing material dosage and performance. Wang et al [ 22 ] used the discrete element method to simulate the damage process of cement-stabilized steel slag subgrade, and the results showed that the energy inside the structure was absorbed and dissipated continuously, and the micro-cracks went through the four stages of emergence, expansion, convergence, and penetration, and finally the structure was completely destroyed.…”
Section: Introductionmentioning
confidence: 99%
“…When steel slag aggregate is used in road subgrade, steel slag is mostly used as an aggregate into the mix, and the performance of the mix is studied accordingly. Li et al [ 21 ] evaluated the feasibility of steel slag used in road subgrade, and analyzed the interaction between different stabilizing materials and steel slag as well as the relationship between stabilizing material dosage and performance. Wang et al [ 22 ] used the discrete element method to simulate the damage process of cement-stabilized steel slag subgrade, and the results showed that the energy inside the structure was absorbed and dissipated continuously, and the micro-cracks went through the four stages of emergence, expansion, convergence, and penetration, and finally the structure was completely destroyed.…”
Section: Introductionmentioning
confidence: 99%
“…Steel slag is a type of industrial solid waste generated by steel-making plants during steelmaking, whose mineralogical composition is comparable to that of cement clinkers, mainly comprising calcium silicate, calcium ferrite, a multi-element solid solution of FeO, MgO, and other divalent metal oxides (RO-phase), free lime ( f -CaO), and periclase ( f -MgO) [ 1 , 2 ]. Although steel slag exhibits some hydration, its current usage in the cement and concrete industry is limited as a mineral admixture or alternative aggregate [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. It is commonly believed that the delayed hydration of f -CaO in steel slag is the primary reason for its poor volume stability [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this rapid expansion has a serious implication since constructing roads consumes many crushed or virgin aggregates, especially for the development of base layers for roads [ 1 ]. A cement-treated base is an example of a stabilized base layer [ 2 ]. It consists of compacted mixtures of granular materials, Portland cement, and water.…”
Section: Introductionmentioning
confidence: 99%